(untitled) (Al-Farooq Journal of Sciences, 2026)
This study presents an empirical document analysis of assessment practices in undergraduate English writing courses at Elmergib University, Libya. The study adopted a document analysis design in which authentic undergraduate examination papers were systematically coded using qualitative content analysis and then analysed using descriptive quantitative techniques. A corpus of 9 examination papers spanning second to fourth year levels was analysed using a purpose designed coding framework. Fifty-nine discrete assessment tasks were identified, coded, and subjected to descriptive statistical analysis across seven variables: task type, writing skill assessed, academic level, examination type, Bloom’s revised taxonomy level, response format, and mark allocation. The results revealed that extended production tasks were the most common type of assessment, accounting for 45.8% of all tasks. Higher-order creative writing tasks (Create) 23.7% were also common, although the examination papers continued to include lower-order metalinguistic knowledge tasks. Paraphrasing, Paragraph Structure Knowledge, Writing Knowledge (Metalinguistic), and Cohesion/Coherence were the most frequently assessed skills, with each making up 10.2% of the assessment tasks. Overall, the examination papers gave limited attention to some important aspects of academic writing, particularly at the fourth-year level, where source integration, evidence synthesis, and other advanced academic writing skills appeared less often. The findings have important implications for improving writing assessment and curriculum design in EFL higher education, particularly in similar undergraduate EFL programmes.